2022
DOI: 10.2147/idr.s371131
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Rifaximin-Containing Regimens for Helicobacter pylori Eradication: Systematic Review – Are They Potential Eradication Regimens?

Abstract: Background Rifaximin, a rifamycin antibiotic, is widely used to treat infectious diarrhea but not commonly used in H. pylori eradication. With its potential advantages of the agent, some studies were conducted on this topic. The aim of this study is to assess effectiveness and safety of rifaximin-containing regimens and to evaluate whether they are alternative choices for H. pylori eradication. Methods Scientific dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
1
1
Order By: Relevance
“…This is in line with other studies [ 136 , 137 ]. These data are completely different from the past; in fact, our group obtained good results (eradication rates always >85%) with the use of levofloxacin and moxifloxacin-based regimens for both treatment-naive and treatment-experienced patients [ 138 , 139 , 140 ].…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…This is in line with other studies [ 136 , 137 ]. These data are completely different from the past; in fact, our group obtained good results (eradication rates always >85%) with the use of levofloxacin and moxifloxacin-based regimens for both treatment-naive and treatment-experienced patients [ 138 , 139 , 140 ].…”
Section: Discussioncontrasting
confidence: 56%
“…Our research group in the past tried to find other molecules to treat H. pylori infection. A trial with rifaximin plus either clarithromycin or levofloxacin and a PPI showed optimal compliance but a limited eradication rate in adult patients when compared to standard first-line treatment [ 140 ].…”
Section: Discussionmentioning
confidence: 99%